2013
DOI: 10.1097/ico.0b013e31827978c8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Collagen Crosslinking on Corneal Sensitivity in Keratoconus Patients

Abstract: Corneal crosslinking performed in keratoconus patients induced a considerable decrease in corneal sensitivity. This decrease was more intense at the first week after the procedure, with a progressive recovery up to 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 20 publications
2
23
0
1
Order By: Relevance
“…Following CXL, corneal sensitivity has been shown to significantly decrease and gradually recover during the first 6 postoperative months [185,186]. No effect on tear secretion or tear film stability was observed [186].…”
Section: Safetymentioning
confidence: 99%
“…Following CXL, corneal sensitivity has been shown to significantly decrease and gradually recover during the first 6 postoperative months [185,186]. No effect on tear secretion or tear film stability was observed [186].…”
Section: Safetymentioning
confidence: 99%
“…Two recent studies reported transient hypoesthesia in keratoconic corneas 6 to 9 months after epi-off CXL. 14,15 To our knowledge, to date there have been no published studies of corneal sensitivity after epi-on CXL. This study evaluated corneal sensitivity in keratoconic eyes following epion and epi-off CXL.…”
Section: Resultsmentioning
confidence: 96%
“…The study detected prominent hypoesthesia 1 month after surgery, which gradually recovered by 9 months after surgery; the time course was similar for both sensitivity restoration and corneal nerve regeneration. Another study (22) evaluated the changes in corneal tactile sensitivity following corneal collagen cross-linking in patients with progressive keratoconus and concluded that corneal CXL performed in keratoconus patients induced a considerable decrease in corneal sensitivity. This decrease was greater in the first week after the procedure, with progressive recovery for up to 6 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%